Dendritic Cell Development in Culture from Thymic Precursor Cells in the Absence of Granulocyte/Macrophage Colony-stimulating Factor - Saunders, Dolores (The Rockefeller University Press, 1996)
The earliest lymphoid precursor population in the adult mouse thymus had previously been shown to produce not only T cells, but also dendritic cell (DC) progeny on transfer to irradiated recipients. In this study, culture of these isolated thymic precursors with a mixture of cytokines induced them to proliferate and to differentiate to DC, but not to T lineage cells. At least 70% of the individual precursors had the capacity to form DC. The resultant DC were as effective as normal thymic DC in the functional test of T cell stimulation in mixed leukocyte cultures. The cultured DC also expressed high levels of class I and class II major histocompatibility complex, together with CD11c, DEC-205, CD80, and CD86, markers characteristic of mature DC in general. However, they did not express CD8α or BP-1, markers characteristic of normal thymic DC. The optimized mixture of five to seven cytokines required for DC development from these thymic precursors did not include granulocyte/macrophage colony stimulating factor (GM-CSF), usually required for DC development in culture. The addition of anti–GM-CSF antibody or the use of precursors from GM-CSF–deficient mice did not prevent DC development. Addition of GM-CSF was without effect on DC yield when interleukin (IL) 3 and IL-7 were present, although some stimulation by GM-CSF was noted in their absence. In contrast, DC development was enhanced by addition of the Flt3/Flk2 ligand, in line with the effects of the administration of this cytokine in vivo. The results indicate that the development of a particular lineage of DC, probably those of lymphoid precursor origin, may be independent of the myeloid hormone GM-CSF.